Management of acute aortic syndrome with evolving individualized precision medicine solutions: Lessons learned over two decades and literature review - Sultan, Sherif; Acharya, Yogesh; Chua Vi Long, Keegan; Hatem, Mohamed; Hezima, Mohieldin; Veerasingham, David; Soliman, Osama; Hynes, Niamh (Frontiers in Surgery, 2023)
Background: Thoracoabdominal acute aortic syndrome is associated with high morbidity and mortality. We aim to scrutinize our evolving strategies for acute aortic syndromes (AAS) management using minimally invasive and adaptive surgical techniques over two decades. Methods: This is a longitudinal observational study at our tertiary vascular centre from 2002 to 2021. Out of 22,349 aortic referrals, we performed 1555 aortic interventions over twenty years. Amongst 96 presented with symptomatic aortic thoracic pathology, 71 patients had AAS. Our primary endpoint is combined aneurysm-related and cardiovascular-related mortality. Results: There were 43 males and 28 females (5 Traumatic Aortic Transection (TAT), 8 Acute Aortic Intramural Hematoma (IMH), 27 Symptomatic Aortic Dissection (SAD) and 31 Thoracic Aortic Aneurysm (TAA) post-SAD) with a mean age of 69. All the patients with AAH received optimal medical therapy (OMT), but TAT patients underwent emergency thoracic endovascular aortic repair (TEVAR). Fifty-eight patients had an aortic dissection, of which 31 developed TAA. These 51 patients with SAD and TAA received OMT initially and interval surgical intervention with TEVAR or sTaged hybrId sinGle lumEn Reconstruction (TIGER). To increase our landing area, we performed a left subclavian chimney graft with TEVAR in twelve patients. The average follow-up duration was 78.2 months, and eleven patients (15.5%) had combined aneurysm and cardiovascular-related mortality. Twenty-six percentages of the patients developed endoleaks (EL), of which 15% required re-intervention for type II and III. Four patients who had paraplegia (5.7%) and developed renal failure died. None of our patients had a stroke or bowel ischaemia. Twenty patients had OMT, eight of these were patients with acute aortic hematoma, and all eight died within 30 days of presentation. Conclusion: Acute aortic hematoma is a sinister finding, which must be closely monitored, and consideration is given to early intervention. Paraplegia and renal failure result in an increased mortality rate. TIGER technique with interval TEVAR has salvaged complex situations in young patients. Left subclavian chimney had increased our landing area and abolished SINE. Our experience shows that minimally invasive techniques could be a viable option for AAS.